Design and test of a half-feed peanut cleaning picker suitable for clay hilly areas in South China - Wang, Shenying; You, Zhaoyan; Xiao, Qiang; Wang, Shengsheng; Luo, Qiaojun; He, Lin (International Journal of Agricultural and Biological Engineering, 2024)
To improve the quality and efficiency of peanut half-feed harvesting in clay hilly areas in South China and address problems such as excessive soil clumps, broken branches, and seedlings in pods, difficulty in cleaning impurities, and the need for manual picking owing to the high soil viscosity and easy hardening, a new half-feed peanut cleaning picker suitable for southern clay hilly areas, including its overall structure and transmission system, was designed. The picker can perform the operations of soil removal, clamping and conveying of seedlings, and orderly pod picking and pod gathering. The structural design of key components and the analysis and determination of key parameters were carried out. By adopting a crank rocker mechanism, a soil removal device was designed. A single-side chain clamping conveying device, which consists of a clamping chain, a pretightening spring, and a guide rail, was designed. A phase tangent configuration of opposite rollers was used to design a pod picking device. Thus, the functions of the half-feed peanut picker, such as cleaning and removing soil, smooth and reliable clamping and conveying, and flexible pod picking, were realized. The field test revealed that when the picking rate was greater than 97%, the soil removal pods drop rate was less than 10%, and the soil removal rate was greater than 50%. The performance indicators meet the design requirements. This study provides a technical reference for the research and development of clean picking technology for upright peanuts in the clay hilly areas of southern China. Key words: peanut, picking device, clamping and conveying device, half-feed, soil removal device, southern clay hilly areasDOI: 10.25165/j.ijabe.20241706.8485Citation: Wang S Y, You Z Y, Xiao Q, Wang S S, Luo Q J, He L. Design and test of a half-feed peanut cleaning picker suitable for clay hilly areas in South China. Int J Agric & Biol Eng, 2024; 17(6): 145–151.